Selected aspects of quality of life in patients with rectal cancer. Part II - individual study - Jabłońska, Iwona (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Background. The paper addresses the quality of life of patients with colorectal cancer who have undergone anterior and low anterior resection of the rectum. The understanding of the quality of life of patients with rectal cancer undergoing anterior resection is still unsatisfactory, which is why we have decided to investigate it. Aim. The aim of the study was to assess the quality of life of patients with a history of rectal cancer with 3-year survival who have undergone anterior resection of the rectum. Material and methods. The study group consisted of patients with B1, B2, C1 and C2 rectal cancer according to Duke’s classification modified by Astler-Coller. The patients underwent anterior resection of the rectum at the First Department of General and Gastrointestinal Surgery at the Jagiellonian University Medical College, Krakow, Poland. The study group consisted of 91 patients. This was a prospective study which employed the diagnostic survey method. Results. A total of 61.5% of the patients with rectal carcinoma who have undergone anterior resection rated their quality of life as good. Of these patients 49.5% rated their health in the previous 2 weeks as “neither good nor bad” and 40.7% of the patients rated their health as good or very good. Conclusions. Based on our study we postulate that a support group should be established for this patient population and that the patient’s quality of life should be of paramount importance when deciding the surgical method.